2009
DOI: 10.1002/ps.1888
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic enzyme(s) confer imidacloprid resistance in a clone of Myzus persicae (Sulzer) (Hemiptera: Aphididae) from Greece

Abstract: A combination of in vitro biochemical assays and in vivo differential synergism studies using PBO and a close analogue EN 16/5-1 suggests that the mechanism conferring increased resistance in this clone is primarily due to enhanced oxidase activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 28 publications
(42 reference statements)
3
65
1
3
Order By: Relevance
“…A previous study examining the susceptibility of the 5191A clone to the pyrethroid α-cypermethrin reported a resistance factor of 33 to this compound which is similar to the level of resistance displayed by other aphid clones with the R3 level of esterase overproduction [13]. However, the enhanced level of carboxylesterase is unlikely to confer significant resistance to neonicotinoids since other M. persicae clones overproducing this enzyme show no resistance to imidacloprid [22].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…A previous study examining the susceptibility of the 5191A clone to the pyrethroid α-cypermethrin reported a resistance factor of 33 to this compound which is similar to the level of resistance displayed by other aphid clones with the R3 level of esterase overproduction [13]. However, the enhanced level of carboxylesterase is unlikely to confer significant resistance to neonicotinoids since other M. persicae clones overproducing this enzyme show no resistance to imidacloprid [22].…”
Section: Discussionmentioning
confidence: 60%
“…However the level of expression between these sequences was variable (ranging from 13–63 fold). This variation probably resulted from the fact that only one of the five ESTs (contig 3118) was a perfect match with FE4 at the probe site, shown previously to be the variant present in 5191A [13]. Therefore, the fold-change indicated by the probe designed on contig 3118 is likely to be the most accurate and this level corresponds well with the 64-fold increase in the esterase level previously reported in aphids with the FE4 genes and R3 levels of resistance [19].…”
Section: Resultsmentioning
confidence: 98%
“…These evidences indicate that the single point mutation (R81T) obtained in this study should be responsible for the imidaclopridresistance in the field population of A. gossypii. P450-mediated detoxification and target site insensitivity have been confirmed to affect the development of imidacloprid resistance in M. persicae [8,9,23]. However, Kool et al reported that the P450, GST and EST detoxification enzymes have no significant differences between the S and IMI-R strains of A. gossypii, and only the nAChRβ1 R81T point mutation has an effect on the imidacloprid resistance of A. gossypii [4].…”
Section: Discussionmentioning
confidence: 94%
“…Some xenobiotics can modulate the activity of not only detoxification enzymes in living organisms, but also of digestive and energy metabolism enzymes (Nath et al ., ; Nath, ; Natsuhara et al ., ; Philippou & Moores, ). Enhanced detoxification activity is frequently associated with insecticide resistance, but the activity of digestive and energy metabolism enzymes may also be important in mitigating fitness costs usually associated with insecticide resistance (Araújo et al ., ,b; Scott, ; Hemingway, ; Silva et al ., ,b).…”
Section: Introductionmentioning
confidence: 99%